On the Assessment of the Flexibility Region in Inter-DSO Local Markets. - Paredes-Parrilla, Ángel; Aguado-Sánchez, José Antonio (My University, 2023)
Renewable Distributed Energy Resources (RDERs) are being rapidly deployed in energy systems to meet net zero emissions objectives. RDERs may cause operational issues in these systems, which exposes both Transmission System Operators (TSOs) and Distribution System Operators (DSOs) to congestions and imbalances. Recently, efforts were made towards the definition of Inter-DSO Local Flexibility Markets (LFMs) to mitigate those issues. However, DSOs do not have properly tools that analyse their flexibility when participating in these markets. This paper presents a linear approach for assessing their flexibility region and the associated costs. The novelty of the proposed approach lies in the flexibility assessment in Inter-DSO LFMs and in the linearization of the problem, which enables the analysis of non-linear DERs such as batteries. The feasibility of the proposed approach is demonstrated using a case study based two IEEE 34 bus systems which represent two different DSOs participating in an Inter-DSO LFM. The flexibility of each DSO is analysed in two scenarios, when the interconnection is active and when it is congested. Results reflect how RDERs can effectively procure flexibility for both situations and how the proposed approach captures their non-linear behaviour.
Keywords: Recursos energéticos renovables; Energía eléctrica - Distribución; Local markets; Flexibility region; DERs; Linear optimization; Inter-DSO markets